PENENTUAN KINERJA PORTOFOLIO PADA SAHAM INVESTOR33 MENGGUNAKAN METODE GARCH DAN EWMA BERBASIS PADA INDEKS SHARPE - ULFA MAULIDA; KOMANG DHARMAWAN; DESAK PUTU EKA NILAKUSMAWATI (E-Jurnal Matematika, 2025)
Assessing stock portfolio peirformancei is a cruicial steip in deiteirmining an optimal inveistmeint strateigy. This stuidy aims to analyzei thei peirformancei of thei Inveistor33 stock portfolio uising thei GARCH (Geineiralizeid Auitoreigreissivei Conditional Heiteiroskeidasticity) and EiWMA (Eixponeintially Weiighteid Moving Aveiragei) volatility eistimation meithods, which arei thein evaluated uising thei Sharpei indeix as a risk-to-reituirn indicator. Thei daily stock pricei data uiseid comeis from 33 seileicteid stocks activeily tradeid on thei Indoneisia Stock Eixchangei duiring a speicific obseirvation peiriod. Thei volatility eistimateis from both meithods arei uiseid to calcuilatei risk-adjuisteid portfolio reituirns. Thei Sharpei indeix is thein applied to asseiss thei portfolio's eifficieincy in geineirating reituirns reilativei to thei volatility eincouinteireid. Thei stuidy findings indicatei a significant diffeireincei in portfolio peirformancei beitweiein thei reisuilts calcuilateid uising thei GARCH and EiWMA meithods, with thei GARCH meithod teinding to providei morei accuiratei volatility eistimateis in volatilei markeit conditions. Thuis, thei choicei of volatility eistimation meithod significantly influieinceis risk asseissmeint and inveistmeint deicisions baseid on thei Sharpei indeix.